Sodium ion positive electrode precursor material and preparation method and application thereof
The sodium ion positive electrode precursor material was prepared by co-precipitation method, and the core and shell components were designed using gradient concentration doping elements, which solved the stability and electrochemical performance problems of nickel-ferromanganese-based materials, and achieved a high capacity and high stability positive electrode Material preparation.
Patent Information
- Application Number
- CN202411048497.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to prepare a nickel-ferromanganese-based gradient concentration precursor and positive electrode material with high spherical shape and high tap density, and the nickel-ferromanganese-based sodium layered oxide faces poor air stability, high potential gas production and charge and discharge irreversible phase change. The problem.
The sodium ion positive electrode precursor material is prepared by co-precipitation method. By designing the different component distributions of the core and shell, using gradient concentration doping elements such as Zn, Cu, Mg, to control the proportion and concentration distribution of elements in the core and shell of the material to achieve Improved material stability and electrochemical properties.
The high Ni components of the material are achieved to participate in charge and discharge, maximize the specific capacity of the positive electrode, and at the same time improve the air stability and cyclic stability of the material without sacrificing capacity, and improve the spherical shape and tap density of the material.
Smart Images

Figure CN119118215A_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of battery technology, and in particular to a sodium ion positive electrode precursor material and a preparation method and application thereof. [Background technology]
[0002] There are many types of positive electrode materials for sodium-ion batteries, including sodium layered oxides, Prussian blue / white, polyanionic compounds, etc. Among them, sodium layered oxides have simple preparation processes, low costs, excellent electrochemical performance, and are highly compatible with existing lithium layered oxide production lines. They are the most promising sodium battery positive electrode materials for industrialization. Especially nickel-iron-manganese-based sodium layered oxides, Ni 2+ →Ni 3+ →Ni 4+ The bivalent state change gives it a higher specific capacity, but nickel-iron-manganese-based sodium layered oxides still face important challenges such as poor air stability, gas generation at high potential, and irreversible phase transition during charge and discharge.
[0003] By doping the fourth component element in the bulk and surface, the local electronic structure and geometric structure of the nickel-iron-manganese-based sodium layered oxide can be finely modulated, thereby reducing the residual alkali on the surface, enhancing the surface oxygen binding force, and inhibiting the phase change during the sodium insertion and extraction process. The fourth component element is usually not electrochemically active, and constant doping in the bulk and surface will seriously reduce the specific capacity of nickel-iron-manganese. Using a gradient concentration design, increasing the surface doping amount to suppress more side reactions on the surface, and reducing the bulk doping amount to maximize the material specific capacity can not only improve the challenges faced by nickel-iron-manganese-based sodium layered oxides, but also minimize the capacity loss caused by doping.
[0004] At present, some technicians have achieved gradient concentration doping of sodium layered oxides through solid-phase sintering, but this technical route is limited by the atomic solid solubility and diffusion rate, making it difficult to achieve precise control of the concentration gradient; and research on preparing gradient concentration precursors by co-precipitation mainly focuses on nickel-cobalt-manganese materials, which are not compatible with nickel-iron-manganese materials, and it is difficult to prepare nickel-iron-manganese-based gradient concentration precursors and positive electrode materials with high sphericity and high tap density. [Summary of the invention]
[0005] In order to solve the problem that it is difficult to prepare a nickel-iron-manganese-based gradient concentration precursor with high sphericity and high tap density in the prior art, the present invention provides a sodium ion positive electrode precursor material and a preparation method and application thereof.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a sodium ion positive electrode precursor material, the chemical formula of which is Ni a F e b Mn c M d (OH)2@Ni a-x F eb Mn c M d+x (OH)2, wherein M is an element doped according to a preset gradient concentration, including one of Zn, Cu, and Mg; 0.2≤a≤0.8, 0 <b≤0.5,0<c≤0.5,0≤d≤0.1,a+b+c+d=1,0<x≤0.2。
[0007] In order to solve the above technical problems, the present invention provides another technical solution as follows: a method for preparing a sodium ion positive electrode precursor material, which is used to prepare the sodium ion positive electrode precursor material as described above, comprising:
[0008] Prepare equal volumes of salt solution 1 and salt solution 2 with Ni:Fe:Mn:M molar ratios of a:b:c:d and (ax):b:c:(d+x) respectively;
[0009] The salt solution 1 is pumped into the alkaline base solution with the precipitant solution and the complexing agent solution at a flow rate k, and the salt solution 2 is pumped into the salt solution 1 at a flow rate k / 3-k / 2, and a coprecipitation reaction is carried out under the protection of an inert gas, and the reaction pH is controlled to change at a uniform rate. After the reaction is completed, the suspension is aged for 2-10 hours to obtain a suspension;
[0010] The sodium ion positive electrode precursor material is obtained by filtering the suspension, washing and drying.
[0011] Preferably, the coprecipitation reaction temperature is 45-65° C., the stirring linear speed is 3-10 m / s, and there is no oxygen exposure during the reaction process.
[0012] Preferably, the initial reaction pH of the coprecipitation reaction is K1, and the pH at the end of the reaction is K2, wherein K1 is Ni a Fe b Mn c M d pH value corresponding to the optimal preparation conditions of (OH)2, K2 is Ni a-x F e b Mn c M d+x pH value corresponding to the optimal preparation conditions of (OH)2.
[0013] Preferably, the molar concentration of the salt solution one and the salt solution two is 2 mol / L; the salt solution one and the salt solution two include any one of sulfate, nitrate or chloride, and any one of ferrous sulfate, ferrous nitrate or ferrous chloride, and 0.1 mol / L of any one of sulfuric acid, hydrochloric acid or nitric acid.
[0014] Preferably, the alkaline base liquid is a mixed solution of ammonia water and hydrazine hydrate, wherein the ammonia concentration is 0.3-2 mol / L, the pH is 10-11, and the hydrazine hydrate concentration is 0.05 mol / L.
[0015] Preferably, the precipitant solution is a mixed solution of sodium hydroxide, ammonia water and hydrazine hydrate; wherein the concentration of sodium hydroxide is 1-10 mol / L, and the concentration of ammonia and the concentration of hydrazine hydrate are consistent with the concentration of ammonia and the concentration of hydrazine hydrate in the alkaline base solution.
[0016] Preferably, the complexing agent is a mixed solution of ammonia water and hydrazine hydrate, wherein the ammonia concentration and the hydrazine hydrate concentration are twice the ammonia concentration and the hydrazine hydrate concentration in the alkaline base solution.
[0017] In order to solve the above technical problems, the present invention provides another technical solution as follows: a sodium ion positive electrode material, which is obtained by mixing the sodium ion positive electrode precursor material as described in any one of the above items with a sodium source and sintering.
[0018] In order to solve the above technical problems, the present invention provides another technical solution as follows: a sodium ion battery, characterized in that: the sodium ion battery comprises the sodium ion positive electrode material as described above.
[0019] Compared with the prior art, the sodium ion positive electrode precursor material and the preparation method and application thereof provided by the present invention have the following beneficial effects:
[0020] 1. A sodium ion positive electrode precursor material provided in an embodiment of the present invention has a chemical formula of Ni a F e b Mn c M d (OH)2@Ni a-x F e b Mn c M d+x (OH)2, the sodium ion cathode precursor material provided in this scheme is divided into an inner core and an outer core, wherein Ni a F e b Mn c M d (OH)2 is the chemical formula of the core, Ni a-x F e b Mn c M d+x(OH)2 is the chemical formula of the outer core. By designing the inner core and the outer shell of the material with different component distributions, the stability of the material can be improved while improving the electrochemical performance. Specifically, by designing the gradient concentration of M, the inner core of the material maintains a high Ni component, while the outer shell gradually increases the content of Mg, Cu or Zn. The inner core maintains a high Ni component to maximize the positive electrode specific capacity, which means that more Ni can participate in the charging and discharging process to provide a larger capacity. While the inner core maintains a high Ni component, by replacing Ni with Mg, Cu or Zn in the outer shell, the stability of the material can be improved without significantly sacrificing capacity. a, b, c, d and x are variables used to describe the relative content of each element in the inner core and the outer shell. a, b, c and d describe the content of Ni, F in the inner core. e, Mn and M ratio, and x describes the increase in M element concentration and the decrease in Ni element concentration from the core to the shell. It is not difficult to understand that by adjusting the value of x, the concentration of M element can be controlled to gradually increase from the core to the shell, while the concentration of Ni element can be gradually reduced. In summary, the sodium ion positive electrode precursor material of this embodiment has uniform phase, concentrated particle size distribution and high tap density. The core is designed to maintain a high Ni component through gradient concentration to maximize the positive electrode specific capacity. At the same time, Mg, Cu or Zn is used to replace Ni on the surface to improve the material's air stability, cycle stability and surface side reactions under high potential.
[0021] 2. An embodiment of the present invention also provides a method for preparing a sodium ion positive electrode precursor material. In this embodiment, salt solution one and salt solution two are prepared by a specific molar ratio to achieve control of the gradient distribution of different components in the material; the co-precipitation rate of different components of the inner core and the outer shell is regulated by controlling the pH change during the reaction, thereby ensuring the gradient concentration distribution of the material during the formation process, thereby improving the sphericity and tap density of the gradient concentration precursor and the positive electrode material, and the preparation process is simple and easy to scale up for production; the co-precipitation reaction is carried out under nitrogen protection to avoid oxidation of metal ions.
[0022] 3. The embodiment of the present invention also provides a method for preparing a sodium ion positive electrode precursor material, wherein the coprecipitation reaction temperature is 45-65° C., the stirring linear speed is 3-10 m / s, and there is no oxygen exposure during the reaction process.
[0023] It should be understood that the absence of oxygen exposure during the reaction process can prevent oxidation of metal ions. Combined with the adjustment of the reaction temperature and stirring speed, the reaction rate can be increased, side reactions can be reduced, and thus the quality of the product can be improved.
[0024] 4. The present invention also provides a method for preparing a sodium ion positive electrode precursor material, wherein the initial pH of the coprecipitation reaction is K1, and the pH at the end of the reaction is K2, wherein K1 is Ni a F e b Mnc M d The pH value corresponding to the optimal preparation conditions of (OH)2 is Ni a F e b Mn c M d The formation of (OH)2 provides the best conditions for the metal ions to precipitate simultaneously and evenly to form complex hydroxides. As the reaction proceeds, the pH value is adjusted to Ni a-x F e b Mn c M d+x The pH value K2 corresponding to the optimal preparation condition of (OH)2 further optimized the Ni a-x F e b Mn c M d+x The formation conditions of (OH)2 are controlled to ensure the precise control of its chemical composition and optimization of its physical structure. The precipitation rate and amount of different metal ions are controlled by adjusting the pH value of the reaction, and the chemical composition and structure of the product are precisely controlled.
[0025] 5. The embodiment of the present invention further provides a sodium ion positive electrode material, which is obtained by mixing the sodium ion positive electrode precursor material as described in any one of the above items with a sodium source and sintering. It has the same beneficial effects as the sodium ion positive electrode precursor material as described in any one of the above items, and will not be repeated here.
[0026] 6. The present invention also provides a sodium ion battery, which includes the sodium ion positive electrode material as described above. It has the same beneficial effects as the sodium ion positive electrode precursor material as described above, and will not be described in detail here.
Brief Description of the Drawings
[0027] Figure 1 It is a flow chart of the steps of a method for preparing a sodium ion positive electrode precursor material provided by the present invention.
[0028] Figure 2 This is a SEM image of the hydroxide precursor material prepared in Example 1 of the present invention.
[0029] Figure 3 This is an EDS point scan of the hydroxide precursor material prepared in Example 1 of the present invention.
[0030] Figure 4 This is the XRD spectrum of the hydroxide precursor material prepared in Example 1 of the present invention.
[0031] Figure 5 This is the XRD spectrum of the gradient concentration positive electrode material prepared in Example 1 of the present invention.
[0032] Figure 6 It is a SEM picture of the hydroxide precursor material prepared in Comparative Example 1 of the present invention.
[0033] Figure 7 This is an S EM image of the hydroxide precursor material prepared in Comparative Example 2 of the present invention.
[0034] Figure 8 This is an S EM image of the hydroxide precursor material prepared in Comparative Example 3 of the present invention.
[0035] Fig. 9 It is an S EM image of the hydroxide precursor material prepared in Comparative Example 4 of the present invention.
[0036] Fig.10 This is an S EM image of the hydroxide precursor material prepared in Example 2 of the present invention.
[0037] Fig.11 This is an S EM image of the hydroxide precursor material prepared in Example 3 of the present invention.
[0038] Fig.12 This is an S EM image of the hydroxide precursor material prepared in Example 4 of the present invention.
[0039] Fig.13 This is an S EM image of the hydroxide precursor material prepared in Example 5 of the present invention. [Specific implementation method]
[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0041] In the embodiments provided by the present invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined according to A. However, it should also be understood that determining B according to A does not mean determining B only according to A, and B can also be determined according to A and / or other information.
[0042] It should be understood that the "one embodiment" or "an embodiment" mentioned throughout the specification means that the specific features, structures or characteristics related to the embodiment are included in at least one embodiment of the present invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. In addition, these specific features, structures or characteristics can be combined in one or more embodiments in any suitable manner. Those skilled in the art should also be aware that the embodiments described in the specification are all optional embodiments, and the actions and modules involved are not necessarily required for the present invention.
[0043] In various embodiments of the present invention, it should be understood that the size of the sequence number of each process does not necessarily mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiment of the present invention.
[0044] The flow chart and block diagram in the accompanying drawings of the present invention illustrate the possible architecture, function and operation of the system, method and computer program product according to various embodiments of the present application. In this regard, each box in the flow chart or block diagram can represent a module, a program segment or a part of a code, and the module, the program segment or a part of the code contains one or more executable instructions for realizing the specified logical function. It should also be noted that in some alternative implementations, the functions marked in the box can also occur in a sequence different from that marked in the accompanying drawings. For example, two boxes represented in succession can actually be executed substantially in parallel, and they can sometimes be executed in the opposite order, which is determined based on the functions involved. It should be particularly noted that each box in the block diagram and / or flow chart, and the combination of the boxes in the block diagram and / or flow chart can be implemented by a dedicated hardware-based system that performs a specified function or operation, or can be implemented by a combination of dedicated hardware and computer instructions.
[0045] The embodiment of the present invention provides a sodium ion positive electrode precursor material, the chemical formula of the sodium ion positive electrode precursor material is Ni a F e b Mn c M d (OH)2@Ni a-x F e b Mn c M d+x (OH)2, wherein M is an element doped according to a preset gradient concentration, including one of Zn, Cu, and Mg; 0.2≤a≤0.8, 0 <b≤0.5,0<c≤0.5,0≤d≤0.1,a+b+c+d=1,0<x≤0.2。
[0046] Specifically, the value range of a includes but is not limited to any one of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or any range between two of them; the value range of b includes but is not limited to any one of 0.1, 0.2, 0.3, 0.4, 0.5 or any range between two of them; the value range of c includes but is not limited to any one of 0.1, 0.2, 0.3, 0.4, 0.5 or any range between two of them. value; the value range of d includes but is not limited to any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or the range between any two of them; the value range of x includes but is not limited to any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or the range between any two of them.
[0047] It should be understood that a, b, c, d and x are variables used to describe the relative content of each element in the core and the shell. a, b, c and d describe the ratio of Ni, Fe, Mn and M in the core, and x describes the increase in the concentration of M element and the decrease in the concentration of Ni element from the core to the shell. By adjusting the value of x, the concentration of M element can be controlled to gradually increase from the core to the shell, while the concentration of Ni element can be gradually reduced.
[0048] It should be noted that the sodium ion cathode precursor is divided into an inner core and an outer core, wherein Ni a F e b Mn c M d (OH)2 is the chemical formula of the core, Ni a-x F e b Mn c M d+x (OH)2 is the chemical formula of the outer core. Ni and Mg elements are distributed in gradient concentrations from the inner core to the outer shell. Specifically, the content of Ni element gradually decreases from the inner core to the outer shell, while the content of Mg element gradually increases from the inner core to the outer shell. By designing the core and outer shell of the material with different component distributions, the stability of the material can be improved while improving the electrochemical performance.
[0049] It can be understood that by gradient concentration design, the core maintains a high Ni component, so that more Ni can participate in the charge and discharge process, maximizing the positive electrode specific capacity. At the same time, Mg, Cu or Zn is used to replace Ni on the surface, which can improve the material's air stability, cycle stability and surface side reactions at high potential without significantly sacrificing capacity.
[0050] Furthermore, the morphology of the sodium ion positive electrode precursor material is a spherical morphology.
[0051] It can be understood that the sodium ion positive electrode precursor material is composed of densely packed thick flake-like primary particles, which specifically presents a spherical morphology with regular morphology and uniform particle size distribution, which helps to obtain a higher tap density during the preparation process.
[0052] Please participate Figure 1 The embodiment of the present invention further provides a method for preparing a sodium ion positive electrode precursor material, which is used to prepare the sodium ion positive electrode precursor material as described in any one of the above items, comprising:
[0053] Step S10: preparing equal volumes of salt solution 1 and salt solution 2 with Ni:Fe:Mn:M molar ratios of a:b:c:d and (ax):b:c:(d+x) respectively;
[0054] Step S20: pumping salt solution 1, precipitant solution and complexing agent solution into the alkaline base solution at a flow rate k, and pumping salt solution 2 into salt solution 1 at a flow rate k / 3-k / 2, performing a coprecipitation reaction under the protection of an inert gas, and controlling the reaction pH to change at a uniform rate, aging for 2-10 hours after the reaction is completed, and obtaining a suspension;
[0055] Step S30: filtering, washing and drying the suspension to obtain a sodium ion positive electrode precursor material.
[0056] Specifically, the protective gas for the coprecipitation reaction includes, but is not limited to, any one or more of helium, xenon, nitrogen, and argon.
[0057] It should be noted that the initial pH of the coprecipitation reaction in step S20 is K1, and the pH at the end of the reaction is K2, wherein the pH value K1 is Ni a F e b Mn c M d The pH value corresponding to the optimal preparation conditions of (OH)2, pH value K2 is Ni a-x F e b Mn c M d+x The pH value corresponding to the optimal preparation conditions of (OH)2 is controlled by controlling the flow rate of the alkaline solution, that is, the precipitant solution, during the reaction process, so as to control the pH value to change uniformly from K1 to K2.
[0058] The initial pH is set to K1 as Ni a F e b Mn c M d The formation of (OH)2 provides the best conditions for the metal ions to precipitate simultaneously and evenly to form complex hydroxides. As the reaction proceeds, the pH value is adjusted to Ni a-x F e bMn c M d+x The pH value K2 corresponding to the optimal preparation condition of (OH)2 further optimized the Ni a-x F e b Mn c M d+x The formation conditions of (OH)2 are controlled to ensure the precise control of its chemical composition and optimization of its physical structure. The precipitation rate and amount of different metal ions are controlled by adjusting the pH value of the reaction, and the chemical composition and structure of the product are precisely controlled.
[0059] In some specific embodiments, after the coprecipitation reaction is completed, aging is required for 2-10 hours, including but not limited to any one of 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of them.
[0060] It can be understood that the sodium ion positive electrode precursor material is prepared by optimizing the crystallization co-precipitation, and the salt solution one and the salt solution two are prepared by a specific molar ratio to achieve the control of the gradient distribution of different components in the material; the co-precipitation rate of different components of the inner core and the outer shell is regulated by controlling the pH change during the reaction, thereby ensuring the gradient concentration distribution of the material during the formation process, thereby improving the sphericity and tap density of the gradient concentration precursor and the positive electrode material, and the preparation process is simple and easy to scale up production; the co-precipitation reaction is carried out under nitrogen protection to avoid the oxidation of metal ions.
[0061] Furthermore, the coprecipitation reaction temperature is 45-65° C., the stirring linear speed is 3-10 m / s, and there is no oxygen exposure during the reaction process.
[0062] Specifically, the temperature of the coprecipitation reaction includes but is not limited to any one of 45°C, 48°C, 50°C, 53°C, 55°C, 58°C, 60°C, 53°C, and 65°C, or a range between any two of them; the stirring linear speed is any one of 3m / s, 4m / s, 5m / s, 6m / s, 7m / s, 8m / s, 9m / s, and 10m / s, or a range between any two of them.
[0063] It should be noted that the coprecipitation reaction is carried out under the protection of nitrogen to isolate oxygen, that is, there is no oxygen involved in the reaction process, thereby preventing the metal ions in the solution from undergoing oxidation reaction with oxygen to generate impurities such as oxides or hydroxides, thereby maintaining the purity and chemical stability of the product; combined with the adjustment of the reaction temperature and the stirring linear speed, the reaction rate can also be increased, side reactions can be reduced, and the quality of the product can be improved.
[0064] Furthermore, the molar concentration of salt solution one and salt solution two is 2 mol / L; salt solution one and salt solution two include any one of sulfate, nitrate or chloride, and any one of ferrous sulfate, ferrous nitrate or ferrous chloride, and 0.1 mol / L of any one of sulfuric acid, hydrochloric acid or nitric acid.
[0065] Furthermore, the alkaline base liquid is a mixed solution of ammonia water and hydrazine hydrate, wherein the ammonia concentration is 0.3-2 mol / L, the pH is 10-11, and the hydrazine hydrate concentration is 0.05 mol / L.
[0066] Specifically, the ammonia concentration of the alkaline base solution includes but is not limited to any one of 0.3mol / L, 0.5mol / L, 0.7mol / L, 0.9mol / L, 1.1mol / L, 1.3mol / L, 1.5mol / L, 1.7mol / L, 1.9mol / L, 2mol / L or a range between any two of them; the pH value includes but is not limited to any one of 10, 10.2, 10.4, 10.6, 10.8, 11 or a range between any two of them.
[0067] Furthermore, the precipitant solution is a mixed solution of sodium hydroxide, ammonia water and hydrazine hydrate; wherein the concentration of sodium hydroxide is 1-10 mol / L, and the concentration of ammonia and the concentration of hydrazine hydrate are consistent with the concentration of ammonia and the concentration of hydrazine hydrate in the alkaline base solution.
[0068] Specifically, the sodium hydroxide concentration of the precipitant solution includes but is not limited to any one of 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, and 10 mol / L, or a range between any two of them.
[0069] Furthermore, the complexing agent is a mixed solution of ammonia water and hydrazine hydrate, wherein the ammonia concentration and the hydrazine hydrate concentration are twice the ammonia concentration and the hydrazine hydrate concentration in the alkaline base solution.
[0070] The embodiment of the present invention further provides a sodium ion positive electrode material, which is obtained by mixing the aforementioned sodium ion positive electrode precursor material with a sodium source and sintering the mixture.
[0071] In some specific embodiments, the sodium source is one or more of sodium hydroxide, sodium carbonate, and sodium nitrate.
[0072] In some specific embodiments, the amount of sodium source used is a molar ratio of Na:TM=0.8-1.02, wherein TM refers to the sodium ion positive electrode precursor material, and the molar ratio of the sodium source to the sodium ion positive electrode precursor material includes but is not limited to any point value of 0.8, 0.85, 0.9, 0.95, 1, 1.01, 1.02 or a range value between any two of them.
[0073] Preferably, the sintering temperature ranges from 650 to 1000°C, including but not limited to any one of 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, and 1000°C, or a range between any two of them; the sintering time is 10 to 24h, including but not limited to any one of 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, and 24h, or a range between any two of them; and the sintering atmosphere is oxygen.
[0074] An embodiment of the present invention further provides a sodium ion battery, which includes the sodium ion positive electrode material as described above.
[0075] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0076] Example 1
[0077] Prepare a salt solution 1 containing 2 mol / L of metal sulfate with a molar ratio of Ni:Fe:Mn=0.33:0.33:0.34 and 0.01 mol / L of sulfuric acid; prepare a salt solution 2 containing 2 mol / L of metal sulfate with a molar ratio of Ni:Fe:Mn:Mg=0.28:0.33:0.34:0.05 and 0.01 mol / L of sulfuric acid; prepare an alkaline solution containing 10 mol / L of sodium hydroxide, 0.5 mol / L of ammonia water and 0.05 mol / L of hydrazine hydrate, i.e., a precipitant solution; prepare an ammonia solution containing 1 mol / L of ammonia water and 0.1 mol / L of hydrazine hydrate, i.e., a complexing agent solution; prepare an alkaline base solution containing 0.5 mol / L of ammonia water and 0.05 mol / L of hydrazine hydrate and adjust the pH to 10.2.
[0078] Inject salt solution 1 and ammonia solution into the reactor containing alkaline bottom solution at a rate of 90 mL / h, maintain the reaction temperature at 50°C, the stirring line speed at 4 m / s, and the reactor is saturated with nitrogen. At the same time, inject salt solution 2 into salt solution 1 at a rate of 45 mL / h and continue stirring. The injection rate of the alkaline solution is controlled by an online pH control system. The total reaction time is 20 hours, and the pH is controlled to increase uniformly from 10.2 to 10.4 during the reaction. Stop adding materials after 20 hours and age for 2 hours under the same conditions. The reactants are filtered and washed to neutrality, dried and sieved to obtain the hydroxide precursor.
[0079] The obtained precursor was fully mixed with sodium hydroxide powder according to TM:Na=1.0, sintered in an oxygen atmosphere at 730°C for 12 hours, and the gradient concentration Mg-doped positive electrode material was obtained after simple crushing and sieving.
[0080] Embodiment 2-5
[0081] The preparation process is the same as that of Example 1, except that the chemical components and process parameters are different. The specific chemical components and process parameters are shown in Table 1.
[0082] Table 1: Technical parameters used in Examples 1-5 and Comparative Examples 1-5
[0083]
[0084]
[0085] Comparative Example 1:
[0086] Prepare a salt solution containing 2 mol / L of metal sulfate with a molar ratio of Ni:Fe:Mn=0.33:0.33:0.34 and 0.01 mol / L of sulfuric acid; prepare an alkaline solution containing 10 mol / L of sodium hydroxide, 0.5 mol / L of ammonia water and 0.05 mol / L of hydrazine hydrate, that is, a precipitant solution; prepare an ammonia solution containing 1 mol / L of ammonia water and 0.1 mol / L of hydrazine hydrate, that is, a complexing agent solution; prepare an alkaline base solution containing 0.5 mol / L of ammonia water and 0.05 mol / L of hydrazine hydrate and adjust the pH to 10.2.
[0087] The salt solution and ammonia solution were injected into the reactor containing the alkaline base liquid at a rate of 90 mL / h respectively, the reaction temperature was maintained at 50°C, the stirring line speed was 4 m / s, and the reactor was saturated with nitrogen. The injection rate of the alkaline solution was controlled by an online pH control system to control the reaction pH to be constant at 10.2. After 20 hours, the addition of materials was terminated, the reactants were filtered and washed to neutrality, and then dried and sieved to obtain the hydroxide precursor.
[0088] The obtained precursor was fully mixed with sodium hydroxide powder according to TM:Na=1.0, sintered in an oxygen atmosphere at 730°C for 12 hours, and the positive electrode material was obtained after simple crushing and sieving.
[0089] Comparative Examples 2-4:
[0090] The preparation process is the same as that of Comparative Example 1, except that the chemical components and process parameters are different. The specific chemical components and process parameters are shown in Table 1.
[0091] To ensure that no environmental factors are introduced, all examples and comparative examples provided in this application are stored in a drying room, and the material morphology / structure characterization, electrode slurry preparation and coating processes are all carried out in a drying room.
[0092] Material morphology / structure characterization test: The tap density is tested by an instrument that complies with the national standards GB / T21354-2008, GB / T5162-2006 and ISO 3953:1993, and the material weighs 5g. The particle size distribution is tested by a laser particle size analyzer, and the test medium is anhydrous ethanol. The air static test is performed by placing the sample in a sealed box containing a saturated magnesium nitrate solution at a static temperature of 20°C.
[0093] Preparation and testing of sodium ion batteries: The sample to be tested was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10, and then an appropriate amount of N-methylpyrrolidone was added and homogenized in a high-speed homogenizer for 10 minutes; the resulting slurry was coated on a clean aluminum foil and dried in a vacuum drying oven at 120°C for 12 hours; after cutting into 14mm diameter pole pieces, sodium metal was used as the counter electrode and 2032 button cells were assembled in a glove box. After standing for 12 hours, the charge and discharge test was carried out using the Blue Electric CT2001 A battery test system, the ambient temperature was 25°C, the voltage window was 2.0-4.0V, the rate test was carried out at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and the cycle test was carried out at 1C.
[0094] The test results of the above embodiments and comparative examples are shown in Table 2 below.
[0095] Table 2
[0096]
[0097] Based on the above examples 1-5 and comparative examples 1-4, Figure 2 and Figure 10-13 It can be seen that the sodium ion positive electrode precursor materials provided in the embodiments of the present invention all present a spherical morphology, the materials are composed of densely packed thick flake-like primary particles, and the tap density of the precursor material is significantly improved compared with the control example. For details, please refer to Table 2.
[0098] See also Figure 2-Figure 5 The sodium ion positive electrode precursor particles provided in this embodiment have Ni and Mg elements with gradient concentration distribution from the core to the shell, and the Ni content gradually decreases from the core to the shell. Correspondingly, the Mg content gradually increases from the core to the shell; the sodium ion positive electrode precursor and its positive electrode material XRD both have high crystallinity, and no obvious impurity phase is generated.
[0099] After standing for 48 hours in an atmosphere with a relative humidity of 55%, the XRD of the gradient concentration cathode material has no obvious change, proving that it has good air stability. It should be understood that the improvement of air stability is conducive to reducing the surface alkali content of the cathode material, thereby improving the gas generation phenomenon during the battery recycling process and improving the cycle stability and safety.
[0100] Please participate Figure 2 and Figure 6 , Figure 7 It can be seen that the sodium ion positive electrode precursor material prepared in Example 1 is composed of spherical secondary particles formed by the accumulation of thick flake primary particles, which is similar to the materials prepared in Comparative Examples 1 and 2; while the precursor or secondary particles prepared by the traditional method are non-spherical, or the primary particles are thin flakes, which can be specifically referred to Figure 8 and Fig. 9 Secondly, the sodium ion positive electrode precursor prepared in Example 1 exhibits a tap density similar to that of Comparative Examples 1 and 2, and a tap density significantly greater than that of Comparative Examples 3 and 4. For details, please refer to Table 2.
[0101] It can be understood that due to the gradient concentration structure design, the cycle stability of the positive electrode material prepared in Example 1 is significantly higher than that of the non-Mg-doped positive electrode material prepared in Comparative Example 1, and the discharge capacity is significantly higher than that of the constant 5 at.% Mg-doped positive electrode material prepared in Comparative Example 2. In summary, replacing Ni with gradient concentration Mg doping can effectively improve the air stability and cycle stability of the positive electrode material and increase its specific capacity.
[0102] See also Figure 10-13 It can be seen from Examples 2-5 that, under different NiFeMn components and different doping elements Zn, Mg, and Cu conditions, the preparation method described in this application can obtain a spherical precursor with high tap density. And due to the gradient concentration structure design, the materials prepared in Examples 2-5 all show good electrochemical performance, and their cycle stability is improved to varying degrees, as shown in Table 2.
[0103] The sodium ion positive electrode precursor material and positive electrode material provided by the present invention maintain a high Ni component in the core through gradient concentration design to maximize the positive electrode specific capacity, and at the same time use Mg / Cu / Zn to replace Ni on the surface to improve the material's air stability, cycle stability and surface side reactions under high potential; the sodium ion positive electrode precursor material preparation method provided by the present invention controls the change of pH during the reaction to achieve the coprecipitation rate under different components of the core and the shell, so as to improve the sphericity and tap density of the gradient concentration sodium ion positive electrode precursor and positive electrode material. Specifically, compared with the traditional solid-phase one-step sintering method, hydrothermal method, sol-gel method, etc., the coprecipitation process and solid-phase sintering method provided by the present invention can achieve atomic-level dispersion of positive electrode material elements at a lower sintering temperature, and at the same time, the concentration gradient of the doped atoms can be regulated.
[0104] Compared with the prior art, the sodium ion positive electrode precursor material and its preparation method and application provided by the present invention have the following beneficial effects:
[0105] 1. A sodium ion positive electrode precursor material provided in an embodiment of the present invention has a chemical formula of Ni a Fe b Mn c M d (OH)2@Ni a-x Fe b Mn c M d+x (OH)2, the sodium ion cathode precursor material provided in this scheme is divided into an inner core and an outer core, wherein Ni a F e b Mn c M d (OH)2 is the chemical formula of the core, Ni a-x F e b Mn c M d+x(OH)2 is the chemical formula of the outer core. By designing the core and shell of the material with different component distributions, the stability of the material can be improved while improving the electrochemical performance. Specifically, by designing the gradient concentration of M, the core of the material maintains a high Ni component, while the outer shell gradually increases the content of Mg, Cu or Zn. The core maintains a high Ni component to maximize the positive electrode specific capacity, which means that more Ni can participate in the charging and discharging process to provide a larger capacity. While the core maintains a high Ni component, by replacing Ni with Mg, Cu or Zn in the outer shell, the stability of the material can be improved without significantly sacrificing capacity. a, b, c, d and x are variables used to describe the relative content of each element in the core and the shell. a, b, c and d describe the ratio of Ni, Fe, Mn and M in the core, while x describes the increase in the concentration of M element from the core to the shell and N It is not difficult to understand the reduction in the concentration of the i element. By adjusting the value of x, the concentration of the M element can be controlled to gradually increase from the core to the shell, while the concentration of the Ni element gradually decreases. In summary, the sodium ion positive electrode precursor material of this embodiment has uniform phase, concentrated particle size distribution, and high tap density. The core is designed with a gradient concentration to maintain a high Ni component to maximize the positive electrode specific capacity. At the same time, Mg, Cu, or Zn is used to replace Ni on the surface to improve the material's air stability, cycle stability, and surface side reactions under high potential.
[0106] 2. An embodiment of the present invention also provides a method for preparing a sodium ion positive electrode precursor material. In this embodiment, salt solution one and salt solution two are prepared by a specific molar ratio to achieve control of the gradient distribution of different components in the material; the co-precipitation rate of different components of the inner core and the outer shell is regulated by controlling the pH change during the reaction, thereby ensuring the gradient concentration distribution of the material during the formation process, thereby improving the sphericity and tap density of the gradient concentration precursor and the positive electrode material, and the preparation process is simple and easy to scale up for production; the co-precipitation reaction is carried out under nitrogen protection to avoid oxidation of metal ions.
[0107] 3. The embodiment of the present invention also provides a method for preparing a sodium ion positive electrode precursor material, wherein the coprecipitation reaction temperature is 45-65° C., the stirring linear speed is 3-10 m / s, and there is no oxygen exposure during the reaction process.
[0108] It should be understood that the absence of oxygen exposure during the reaction process can prevent oxidation of metal ions. Combined with the adjustment of the reaction temperature and stirring speed, the reaction rate can be increased, side reactions can be reduced, and thus the quality of the product can be improved.
[0109] 4. The present invention also provides a method for preparing a sodium ion positive electrode precursor material, wherein the initial pH of the coprecipitation reaction is K1, and the pH at the end of the reaction is K2, wherein K1 is Ni a F e b Mnc M d The pH value corresponding to the optimal preparation conditions of (OH)2 is Ni a F e b Mn c M d The formation of (OH)2 provides the best conditions for the metal ions to precipitate simultaneously and evenly to form complex hydroxides. As the reaction proceeds, the pH value is adjusted to Ni a-x F e b Mn c M d+x The pH value K2 corresponding to the optimal preparation condition of (OH)2 further optimized the Ni a-x F e b Mn c M d+x The formation conditions of (OH)2 are controlled to ensure the precise control of its chemical composition and optimization of its physical structure. The precipitation rate and amount of different metal ions are controlled by adjusting the pH value of the reaction, and the chemical composition and structure of the product are precisely controlled.
[0110] 5. The embodiment of the present invention further provides a sodium ion positive electrode material, which is obtained by mixing the sodium ion positive electrode precursor material as described in any one of the above items with a sodium source and sintering. It has the same beneficial effects as the sodium ion positive electrode precursor material as described in any one of the above items, and will not be repeated here.
[0111] 6. The present invention also provides a sodium ion battery, which includes the sodium ion positive electrode material as described above. It has the same beneficial effects as the sodium ion positive electrode precursor material as described above, and will not be described in detail here.
[0112] The above is a detailed introduction to a sodium ion positive electrode precursor material and its preparation method and application disclosed in an embodiment of the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sodium ion cathode precursor material, Features: The chemical formula of the sodium ion positive electrode precursor material is Ni a F e b Mn c M d (OH) 2 @Ni a-x F e b Mn c M d+x (OH) 2 , where M is an element doped according to a preset gradient concentration, including one of Zn, Cu, and Mg; 0.2≤a≤0.8, 0 <b≤0.5,0<c≤0.5,0≤d≤0.1,a+b+c+d=1,0<x≤0.2。 2. A method for preparing a sodium ion positive electrode precursor material, for preparing the sodium ion positive electrode precursor material as claimed in claim 1, It is characterized in that include: Prepare equal volumes of salt solution 1 and salt solution 2 with Ni:Fe:Mn:M molar ratios of a:b:c:d and (ax):b:c:(d+x) respectively; The salt solution 1 is pumped into the alkaline base solution with the precipitant solution and the complexing agent solution at a flow rate k, and the salt solution 2 is pumped into the salt solution 1 at a flow rate k / 3-k / 2, and a coprecipitation reaction is carried out under the protection of an inert gas, and the reaction pH is controlled to change at a uniform rate. After the reaction is completed, the suspension is aged for 2-10 hours to obtain a suspension; The sodium ion positive electrode precursor material is obtained by filtering the suspension, washing and drying.
3. The method for preparing the sodium ion positive electrode precursor material according to claim 2, Features: The coprecipitation reaction temperature is 45-65° C., the stirring linear speed is 3-10 m / s, and there is no oxygen exposure during the reaction process.
4. The method for preparing the sodium ion positive electrode precursor material according to claim 2, Features: The initial reaction pH of the coprecipitation reaction is K1, and the pH at the end of the reaction is K2, wherein K1 is Ni a F e b Mn c M d (OH) 2 The pH value corresponding to the optimal preparation conditions, K2 is Ni a-x F e b Mn c M d+x (OH) 2 The pH value corresponding to the optimal preparation conditions.
5. The method for preparing the sodium ion positive electrode precursor material according to claim 2, Features: The molar concentration of the salt solution 1 and the salt solution 2 is 2 mol / L; the salt solution 1 and the salt solution 2 include any one of sulfate, nitrate or chloride, and any one of ferrous sulfate, ferrous nitrate or ferrous chloride, and 0.1 mol / L of any one of sulfuric acid, hydrochloric acid or nitric acid.
6. The method for preparing the sodium ion positive electrode precursor material according to claim 2, Features: The alkaline base liquid is a mixed solution of ammonia water and hydrazine hydrate, wherein the ammonia concentration is 0.3-2 mol / L, the pH is 10-11, and the hydrazine hydrate concentration is 0.05 mol / L.
7. The method for preparing the sodium ion positive electrode precursor material according to claim 6, Features: The precipitant solution is a mixed solution of sodium hydroxide, ammonia water and hydrazine hydrate; wherein the concentration of sodium hydroxide is 1-10 mol / L, and the concentration of ammonia and the concentration of hydrazine hydrate are consistent with the concentration of ammonia and the concentration of hydrazine hydrate in the alkaline base solution.
8. The method for preparing the sodium ion positive electrode precursor material according to claim 6, Features: The complexing agent is a mixed solution of ammonia water and hydrazine hydrate, wherein the ammonia concentration and the hydrazine hydrate concentration are twice the ammonia concentration and the hydrazine hydrate concentration in the alkaline base solution.
9. A sodium ion positive electrode material, Features: The sodium ion positive electrode material is obtained by mixing the sodium ion positive electrode precursor material as claimed in claim 1 with a sodium source and sintering.
10. A sodium ion battery, Features: The sodium ion battery comprises the sodium ion positive electrode material as claimed in claim 9.
Citation Information
Cited By
O3 type layered oxide sodium ion positive electrode material and preparation method and application thereof
CN120565664A
Element gradient doped lithium-rich manganese-based positive electrode material and preparation method thereof
CN122417759A
